Bone and inflammatory responses to training in female rowers over an Olympic year - Kurgan, N.; Logan-Spencer, H.; Falk, B.; Klentrou, P. (Medicine & Science in Sports & Exercise, 2018)
Introduction/Purpose To examine whether fluctuations in training load during an Olympic year lead to changes in bone mineral densities and factors that regulate bone (sclerostin, osteoprotegerin and receptor activator of nuclear factor kappa-B ligand), energy metabolism (insulin-like growth factor-1 and leptin), and inflammation (tumor necrosis factor-a and interleukin 6) in elite heavyweight female rowers.